Perlindungan Hukum Terhadap PPAT yang Diberhentikan Tidak Hormat dalam Keputusan MPPD dalam Kaitannya dengan Putusan MA No. 337 K/TUN/2021 jo. Putusan PK No. 65 PK/TUN/2023 - Tumbur Yoel Rivaldo; Hasim Purba; Rudy Haposan Siahaan (CV Rewang Rencang, 2025)
PPAT, as an official who serves the public in land affairs, requires adequate legal protection. However, cases of unfair dismissal with disgrace by MPPD continue to occur, often disregarding settlements reached between the disputing parties. The limitations of MPPD's authority in imposing dismissal with disgrace based on the principles of proportionality and appropriateness; the legal standing of reconciliation between the complainant and the reported PPAT in relation to MPPD’s decision: and the forms of legal protection available to PPAT dismissed with disgrace based on the aforementioned court rulings. This research employs a normative legal research method. The results indicate that the authority of MPPD must be constrained by the principles of proportionality and appropriateness, considering the balance between the seriousness of the violation and the sanction imposed, as well as mitigating factors such as reconciliation and withdrawal of complaints. This study concludes that dismissal with disgrace without considering reconciliation and mitigating factors constitutes a violation of the principle of justice and may be annulled by the court.